Problematika Konsep Diskresi dalam Penyelenggaraan Administrasi Pemerintahan pasca Undang-Undang Cipta Kerja - Nurmayani; Mery Farida (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2021)
Purpose: The enactment of Law No. 11 of 2020 on Job Creation has modified several provisions governing government administration, one of which concerns discretion. Discretion, defined as the freedom of action of government officials when acting or making decisions, is redefined in the Job Creation Law, as the previous definition was deemed to obstruct investment by defining discretion as limited discretion. The community criticizes discretion, but the Job Creation Law's discretion is due to the numerous problems associated with this concept. Research Methodology: The study's problem formulation is as follows: How is the concept of discretion applied to government administration following the Job Creation Act? What issues arise as a result of the Job Creation Act's change in the concept of discretion? This legal research employs a normative juridical research methodology that combines a statutory and conceptual approach to map the concept of discretion in the Law on Job Creation and the resulting problems. Results: The Employment Creation Act expanded the concept of discretion by eliminating discretionary requirements that are inconsistent with applicable laws and regulations, resulting in several issues, including the possibility of issuing unconstitutional discretion, discretion that is inconsistent with the AUPB, and a concept of discretion that is too broad, disproportionate to the supervision of discretionary officials.